Assessing the Stroke-Specific Quality of Life for Outcome Measurement in Stroke Rehabilitation: Minimal Detectable Change and Clinically Important Difference - Wu Ching-yi; Fu Tiffany; Lin Keh-chung; Hsieh Ching-ju (Health and Quality of Life Outcomes, 2011)
Abstract Background This study was conducted to establish the minimal detectable change (MDC) and clinically important differences (CIDs) of the physical category of the Stroke-Specific Quality of Life Scale in patients with stroke. Methods MDC and CIDs scores were calculated from the data of 74 participants enrolled in randomized controlled trials investigating the effects of two rehabilitation programs in patients with stroke. These participants received treatments for 3 weeks and underwent clinical assessment before and after treatment. To obtain test-retest reliability for calculating MDC, another 25 patients with chronic stroke were recruited. The MDC was calculated from the standard error of measurement (SEM) to indicate a real change with 95% confidence for individual patients (MDC95). Distribution-based and anchor-based methods were adopted to triangulate the ranges of minimal CIDs. The percentage of scale width was calculated by dividing the MDC and CIDs by the total score range of each physical category. The percentage of patients exceeding MDC95 and minimal CIDs was also reported. Results The MDC95 of the mobility, self-care, and upper extremity (UE) function subscales were 5.9, 4.0, and 5.3 respectively. The minimal CID ranges for these 3 subscales were 1.5 to 2.4, 1.2 to 1.9, and 1.2 to 1.8. The percentage of patients exceeding MDC95 and minimal CIDs of the mobility, self-care, and UE function subscales were 9.5% to 28.4%, 6.8% to 28.4%, and 12.2% to 33.8%, respectively. Conclusions The change score of an individual patient has to reach 5.9, 4.0, and 5.3 on the 3 subscales to indicate a true change. The mean change scores of a group of patients with stroke on these subscales should reach the lower bound of CID ranges of 1.5 (6.3% scale width), 1.2 (6.0% scale width), and 1.2 (6.0% scale width) to be regarded as clinically important change. This information may facilitate interpretations of patient-reported outcomes after stroke rehabilitation. Future research is warranted to validate these findings.